Diagnóstico socioeconômico e ambiental das construtoras do município de Pau dos Ferros-RN - Linhares, Ravi da Silva (Universidade Federal Rural do Semi-Árido, 2018)
The first purpose of business is to make a profit. With the transformation in production models, new variables were included in this perspective, such as the insertion of the environmental dimension in business decisions. The present research has as objective to carry out a socioeconomic and environmental diagnosis of the constructors of the municipality of Pau dos Ferros-RN. As methodological procedures, a qualitative and quantitative analysis was carried out, with an exploratory character, with the application of semi-structured questionnaires in 10 (ten) constructors in the mentioned municipality. The results showed that the majority of the investigations are small. It was also observed that the analyzed establishments present deficiencies related to the consumption of water and electric energy, and in the management of solid wastes and liquid effluents. In order to do so, it is pointed out environmental management actions to mitigate the aforementioned problem: how to elaborate a system of reuse of water; manage solid wastes and liquid effluents; carry out selective garbage collection; apply training to employees; and implement an Environmental Management System.
Keywords: Construção civil; Sustentabilidade; Gestão ambiental empresarial; ENGENHARIAS::ENGENHARIA CIVIL